PATH-06. A TARGETED NGS-BASED OVERALL SOLUTION TO SUPPORT DIAGNOSTICS AND THERAPY PREDICTION IN NEUROONCOLOGY: CONSIDERATIONS FOR A FLEXIBLE AND COST-EFFICIENT PLATFORM CHOICE AND PANEL DESIGN. (11th November 2019) - Riemenschneider, Markus; Rudolf, Andras; Hau, Peter; Pukrop, Tobias; Kölbl, Oliver; Corbacioglu, Selim; Brawanski, Alexander; Proescholdt, Martin; Lorenz, Julia
Abstract: Continuous updates add novel molecular markers to the WHO classification of CNS tumors. Additionally, molecularly informed trials may provide the basis for the introduction of additional predictive biomarkers. All these developments will prospectively require molecular testing to a yet unknown extent and still pose challenges to many neuropathology labs. Some of the relevant alterations (e.g. C11orf95-RELA) are hard to assess or complex subclassifications (e.g. for medulloblastomas) are required. Some labs rely on a two-tiered approach: i) methylation arrays for tumor classification and ii) targeted NGS panel sequencing for identifying actionable mutations. However, high initial investment and annual costs for running two platforms in parallel hinder a fast expansion of the new techniques in the breadth of neuropathology. We decided to focus on the sole use of the relatively cost-efficient Mini-Seq NGS platform (Illumina). First, we designed a DNA panel (FFPE, HaloPlex, Agilent; no Covaris required) that is suited for detection of DNA mutations, copy number alterations and chromosomal alterations (459 kbp, 58 genes, 4082 SNPs, 98.83% coverage). We successfully used this platform to support tumor classification in astrocytomas, oligodendrogliomas, meningiomas and medulloblastomas and identified actionable targets of clinical use. We then designed a RNA panel (FFPE, Sure Select, Agilent) that detects gene fusions and covers a broad range of alterations particularly relevant to pediatric tumors (e.g. pediatric glioblastomas, ependymomas, CNS PNETs) (148 kbp, coding sequence of 31 genes, 99.88% coverage). With these two panels we cover the most relevant molecular alterations in the field of neurooncology. The cost-efficient and flexible single platform approach enables state-of-the-art molecular diagnostics in virtually every neuropathology lab in a quality-controlled manner. Functionality is guaranteed for future revisions of the WHO classification as novel biomarkers can be easily included in an adapted panel design.